Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure! Let's simplify the expression \((3x + 2)^2\) step-by-step.
### Step 1: Write the expression out in expanded form
The given expression is \((3x + 2)^2\).
To expand this, we can use the formula for the square of a binomial:
[tex]\[ (a + b)^2 = a^2 + 2ab + b^2 \][/tex]
Here \(a = 3x\) and \(b = 2\). So, we substitute \(a\) and \(b\) into the formula:
### Step 2: Apply the formula
Let's break it down into parts:
[tex]\[ (3x + 2)^2 = (3x)^2 + 2(3x)(2) + (2)^2 \][/tex]
### Step 3: Compute each term individually
1. First term: \((3x)^2 = 9x^2\)
2. Second term: \(2(3x)(2) = 12x\)
3. Third term: \((2)^2 = 4\)
### Step 4: Combine all terms
Combine all the terms to write the expanded form:
[tex]\[ 9x^2 + 12x + 4 \][/tex]
So, the simplified expression for \((3x + 2)^2\) is:
[tex]\[ 9x^2 + 12x + 4 \][/tex]
### Step 5: Identify the coefficients
In the expression \(9x^2 + 12x + 4\):
- The coefficient of \(x^2\) is \(9\).
- The coefficient of \(x\) is \(12\).
- The constant term is \(4\).
Therefore, the expanded form of the expression \((3x + 2)^2\) is:
[tex]\[ 9x^2 + 12x + 4 \][/tex]
### Step 1: Write the expression out in expanded form
The given expression is \((3x + 2)^2\).
To expand this, we can use the formula for the square of a binomial:
[tex]\[ (a + b)^2 = a^2 + 2ab + b^2 \][/tex]
Here \(a = 3x\) and \(b = 2\). So, we substitute \(a\) and \(b\) into the formula:
### Step 2: Apply the formula
Let's break it down into parts:
[tex]\[ (3x + 2)^2 = (3x)^2 + 2(3x)(2) + (2)^2 \][/tex]
### Step 3: Compute each term individually
1. First term: \((3x)^2 = 9x^2\)
2. Second term: \(2(3x)(2) = 12x\)
3. Third term: \((2)^2 = 4\)
### Step 4: Combine all terms
Combine all the terms to write the expanded form:
[tex]\[ 9x^2 + 12x + 4 \][/tex]
So, the simplified expression for \((3x + 2)^2\) is:
[tex]\[ 9x^2 + 12x + 4 \][/tex]
### Step 5: Identify the coefficients
In the expression \(9x^2 + 12x + 4\):
- The coefficient of \(x^2\) is \(9\).
- The coefficient of \(x\) is \(12\).
- The constant term is \(4\).
Therefore, the expanded form of the expression \((3x + 2)^2\) is:
[tex]\[ 9x^2 + 12x + 4 \][/tex]
Answer:
hello
Step-by-step explanation:
we knox : (a+b)²=a²+2ab+b²
so (3x+2)²
a=3x, a²=9x²
b=2, b²=4
2ab=2*3x*2 =12x
(3x+2)²= 9x²+12x+4
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.